Effect of downhill walking training on neuromuscular variables - Thiago Pires de Oliveira; Leonardo Coelho Rabello de Lima; Felipe Bruno Dias de Oliveira; Benedito Sérgio Denadai; Camila Coelho Greco (Universidade Federal de Santa Catarina, 2018)
Walking involves small adjustments to maintain body balance. However, the demand for these adjustments may be different during downhill walking. The aim of this study was to analyze the effect of periodized downhill walking training on neuromuscular responses of knee flexors (KF). Seventeen active males (Age = 22.9 ± 3.9 years) were randomly assigned into two groups: control, level walking (CG, N = 8) and downhill walking (DWG, N = 9). Individuals performed the following procedures, in different days: 1) Maximal voluntary contractions to determine peak torque (PT) and rate of torque development (RTD) at different time intervals from the onset of muscle contraction. The test was performed before (Pre) and after (Post) a 4-week downhill walking training period. PT and peak RTD did not change after the training period (p > 0.05). However, there was significant increase in RTD at 150 ms and 200 ms after the onset of muscle contraction (p < 0.05). Additionally, the electromyographic activity (root mean square) of the biceps femoris and semitendineous muscles presented an increase after the training period (p < 0.05). Thus, downhill walking training can promote improvement RTD and muscle activity in the late phase of muscle contraction, which can have important implications during downhill walking, in which a rapid action of KF can help body balance against the disturbance generated by the slope.